Issues in Electronic Banking : An Overview - Schaechter, Andrea (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2002)
Using electronic delivery channels for banking services and products has become increasingly popular in recent years. Electronic banking makes it possible to offer banking services around the world 24 hours a day. The dependence on technology for providing the services with the necessary security, and the cross-border nature of transactions, involve additional risks for banks and new challenges for banking regulators and supervisors. This paper provides an overview of some of the issues resulting from the development of electronic banking and how they are currently being addressed by regulatory and supervisory authorities.